Comparison Of The Lyrics Of The Song Rudang-Rudang Kegeluhen Of The Karo Batak Ethnic With The Song Margogo Ijur Bari Of The Toba Batak Ethnic - Hutauruk, Febri Ola; Saragih, Dinda Apriani; Sitompul, Yulia Saftania; Sinulingga, Jekmen (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to examine the intrinsic elements and identify the similarities and differences in the lyrics of the song Rudang-Rudang Kegeluhen Ethnik Batak Karo with the lyrics of the song Margogo Ijur Bari Ethnik Batak Toba. This study is included in the type of qualitative descriptive research with a comparative literature approach. The data collection technique used is the reading and note-taking technique. The researcher read both song lyrics and noted the similarities and differences between the two song lyrics. The data analysis technique uses an interactive technique that includes the process of data reduction, data display and drawing conclusions. The results of the study show that the two songs have similarities and differences. The similarities between the two songs lie in the character values of a child expressing gratitude and appreciation for their parents for their love and sacrifice. The differences between the two songs can be seen in terms of the story that the lyrics of the song Rudang-rudang kegeluhen tell more about a child who realizes how important the role of parents is in his life. In addition, the lyrics of the song Margogo Ijur Bari tell of a child expressing gratitude for the love, sacrifice, and character that has been given by his parents.